The Effect of the Death of a Child on Midlife Mental and Physical Health: An Exploration of Risk and Resilience Factors - Rogers, Catherine Hilary (2005)
The study examined the long-term effects of a death of a child on a variety of parental psychological and physical outcomes, incorporating several methodological and conceptual innovations over previous research. Prior bereavement research typically has focused on functioning within a short time period after the death and often has utilized self-selected samples of grieving parents; thus current models of grief may be inadequate. In contrast, this study broadened the timeframe in which bereavement is studied (average time since death= 20 years), and examined a sample of bereaved parents who were not self-selected. Participants were members of the Wisconsin Longitudinal Study (713 bereaved and 713 non-bereaved parents) who were assessed in 1957, 1975/77, and 1992/94 and were matched on family of origin demographic variables. Results show that bereaved parents reported a higher sense of purpose in life than non-bereaved parents. Further, higher levels of purpose in life was associated with lower levels of depression in bereaved parents, and with lower levels of physical illness in bereaved men. As expected, bereaved parents exhibited higher levels of depression than non-bereaved parents. For bereaved women, having someone with whom to share private thoughts and feelings was correlated with higher levels of depression, indicating that social support may be sought when functioning is poor. Higher job satisfaction was associated with lower levels of depression in bereaved women suggesting that role variegation is a factor promoting resiliency. Further, having another child after the death of a child was associated with lower levels of depression for bereaved women. Contrary to expectations, having other children in the home at the time of death was associated with lower social support and higher divorce rates for bereaved women. In sum, the current study suggests that the negative effects of the death of a child are longstanding. Several factors (e.g., purpose in life, role variegation) may promote resiliency and thus merit more scientific study and clinical attention